A SYSTEMATIC EVALUATION TOOL FOR HERITAGE SHOPHOUSE FACADES - Wan Ali, Wan Nordiana; Ahmad, A Ghafar (PLANNING MALAYSIA, 2022)
Heritage shophouses are the architectural asset that becomes a landmark of many heritage areas, particularly in major towns in Malaysia. This cultural heritage needs to be preserved or conserved to prolongs its life. However, there is still a need for in-depth study on the architectural part as to add knowledge about this heritage treasure. Thus, this paper tends to develop a definitive list of the architectural characters of the heritage shophouse façades according to its elements. The definitive list was outlined by referring and comparing data extracted from the local government reports, books, articles, and research undertaken by scholars in architecture and conservation. Furthermore, a fieldwork had been conducted at the Heritage Area of Ipoh involving 121 shophouses by using a checklist to support the secondary data. Thematic analysis was applied by sorting all architectural characters into five main categories of elements that include structural, building enclosure, opening, fenestration, and ornamentation. Later, a matrix taxonomy of architectural styles was developed to form an evaluation tool as an innovation to the existing inventory and documentation method for the heritage shophouses. The paper concludes that the concise data of architectural characters are significant to differentiate the styles of the heritage shophouse façade. Further research at other heritage areas in Malaysia should be conducted to gain more data of other architectural styles.